Instrumentación contractual de una operación de adquisición de acciones o activos - Artagaveytia, Pablo A. (2023)
The acquisition of shares is a complex process that challenges the negotiation capacity of the parties. It is natural that both the buyer and the seller look for tools that help them to reduce, if not eliminate, any type of risk to their interests, thus, from Civil and Commercial Law we find procedures, clauses, covenants, guarantees and among other conditions that if used properly could ensure the acquisition of a good business.Focusing on the diversity of situations under which a purchase and sale can be carried out, the author analyzes the strengths and weaknesses of the adjustment tools that are useful to successfully face the world of transactions.